Development of manufacturing engineering program of Bulacan State University using employability tracer study - Cyrus Lawrence Camancho Bual; Rachel Cunanan Bual (International Journal of Evaluation and Research in Education (IJERE), 2024)
Tracer study is one of the continuous quality improvement tools for curriculum development. The graduates are invited to answer the tracer form to determine their employability. Since the Manufacturing Engineering program in Bulacan State University (BuLSU) is the youngest engineering program, there is minimal data on graduates available, especially on the details of their first jobs, such as the first job related to the program, time taken to land their first job, gross monthly salary, and learning competencies. The demographic profile of the manufacturing engineering graduates from 2015 to 2019 is preserved and remains strictly confidential for the safety of their identification. Correspondingly, the study applied a cross-sectional retrospective survey method. Moreover, 67.41% of manufacturing engineering graduates responded. The employment rate of manufacturing engineering graduates was 93.38%, whereas regular or permanent in their current employment was 84.40%. Furthermore, data show that they are employed within less than a month, 50.97% of responses. Lastly, the primary learning competency that manufacturing engineering graduates consider is critical thinking skills, with a response rate of 86.11%, followed by problem-solving skills, with 81.94% responses, while third was communication skills, with a rate of 78.08%. Ultimately, the recommendations for further curriculum and program improvement are exhibited.